Análisis del cumplimiento tributarío de una empresa dedicada a la fabricación y comercialización de rollos y fundas plásticas para productos de consumo masivo ubicada en la ciudad de Guayaquil durante el período fiscal 2008. - Quevedo, Katherine (2010)
This article is about the tax analysis done to a company that trades plastic bags in Guayaquil city, being its goal to prove if it has been meeting its tax obligations and dealing properly with its possible fiscal risks. Besides, it describe the tests used to detect these risks as the statistical analysis of its main items such as sales, suppliers, etc., resulting from this a complete tax history through the revision of the declaration of income presented to SRI. Additionally the company’s financial analysis is described in order to have a wider vision of its development since it began operating and of its growth that it has been keeping through the years.